The role of intraoral abrasion pressure with alumunium oxide on the bond strength of resin cement in adhesive bridge restorations - Putri Welda Utami Ritonga; Haslinda Z. Tamin; Uliani, Hanna Mentari (Indonesia Prosthodontic Association, 2024)
Background: Adhesive bridge is a fixed denture with minimal abutment preparation attached with resin cement. Exposure of the dentin during preparation in the posterior region causes frequent detachment of the adhesive bridge. This is due to the presence of fluid and changes in the smear layer on the dentinal tubules, to increase bond strength, the intraoral abrasion method was developed. Intraoral abrasion is a mechanical technique using air and water sprays to produce tooth surface roughness while increasing bond strength without damaging the tooth structure. Objective: One of the intraoral abrasion materials used is aluminum oxide (Al2O3). One of the operating parameters of intraoral abrasion that can affect bond strength between resin cement and the tooth surface is pressure. Optimal intraoral abrasion pressure with Al2O3 and the right type of resin cement aims to create tooth surface roughness while increasing the bond strength of resin cement in adhesive bridge restorations. Conclusions: The success of adhesive bridges, especially in the posterior area, cannot be separated from the role of optimum intraoral abrasion pressure on the tooth surface. The correct use of intraoral abrasion pressure can increase the bond strength of resin cement on the tooth surface while reducing tooth structure damage. Keywords: adhesive bridge, adhesive resin cement, intraoral abrasion, alumunium oxide, water airborne abrasion.